Comparison of Technical Efficiency and Socio-economic Status in Animal-crop Mixed Farming Systems in Dry Lowland Sri Lanka - Vithanage, Upul Yasantha Nanayakkara; Gunaratne, Lokugam H. P; M. B. P, Kumara Mahipala; Cyril, Hewa Waduge (Asian Journal of Agriculture and Rural Development, 2014)
Pre-tested, structured questionnaires covered management aspects, inputs, outputs, socio-economic situations and constraints in dairy farming among Semi-intensive (SIFS) and Extensive farming systems (EFS) in dry-lowland Sri Lanka. Parametric data were analyzed using two-tailed‘t’ and ‘Z’ tests, and non-parametric values were analyzed using Chi-square and Fisher’s extract tests. Cobb-Douglas model was used to calculate meta-frontier and system-specific frontiers. Returns in SIFS are lower than EFS. Labor costs are 91.72% and 87.26% in EFS and SIFS respectively. Counting family labor, SIFS has no comparative surplus. Excluding this, dairying is profitable even in SIFS. Dairying provides EFS family insurance where selling animals increases income. Discouragement of this in SIFS impacts negatively on sustainable income. Integration is comparatively minimal in EFS. Established with the best practices and technologies available, SIFS requires external resources to enhance efficiencies. If all EFS farmers achieved best farmer TE, output could increase by 45.09%. Similarly, SIFS output could increase by 57.08%. Farmer education and training programs contribute to improved production efficiency. Grassland scarcity and low productivity affect output adversely; poor veterinary and extension services are major constraints. Farmers consider dairying as profitable, which secures its future. Contrastingly, 35.19% of farmers believe it is low status, preferring professional jobs despite lower comparative incomes.